2021
DOI: 10.3390/cancers13112719
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic and Metabolomic Integration Reveals Dynamic Metabolic Regulation in Bladder Cancer

Abstract: Bladder cancer (BC) represents a clinical, social, and economic challenge due to tumor-intrinsic characteristics, limitations of diagnostic techniques and a lack of personalized treatments. In the last decade, the use of liquid biopsy has grown as a non-invasive approach to characterize tumors. Moreover, the emergence of omics has increased our knowledge of cancer biology and identified critical BC biomarkers. The rewiring between epigenetics and metabolism has been closely linked to tumor phenotype. Chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 258 publications
(389 reference statements)
0
7
0
Order By: Relevance
“…miRNA usually possesses the capacity of binding multiple target genes 25 . In mammalian cells, it is universally acknowledged that miRNAs are at least partially complementary to the 3′‐UTR of the target mRNA molecule to mediate the target gene expression at the posttranscriptional level 26 . KLF9 belongs to the KLF transcriptional factor family, and it was reported to participate in the progression of ovarian cancer and BC 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA usually possesses the capacity of binding multiple target genes 25 . In mammalian cells, it is universally acknowledged that miRNAs are at least partially complementary to the 3′‐UTR of the target mRNA molecule to mediate the target gene expression at the posttranscriptional level 26 . KLF9 belongs to the KLF transcriptional factor family, and it was reported to participate in the progression of ovarian cancer and BC 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…25 In mammalian cells, it is universally acknowledged that miRNAs are at least partially complementary to the 3 0 -UTR of the target mRNA molecule to mediate the target gene expression at the posttranscriptional level. 26 KLF9 belongs to the KLF transcriptional factor family, and it was reported to participate in the progression of ovarian cancer and BC. 27,28 Yang et al reported that KLF9 had lower expression in BC and was a targeted gene of miR-17-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the genomic/transcriptomic approaches, metabolomic analyses of urine specimens, the availability of the Human Metabolome Database, and the bulk epigenome analyses approaches have identified altered pathways in BC, some of which are likely associated with bladder carcinogenesis, growth, and progression to MIBC. Recent reviews describe these discoveries [ 178 , 179 , 180 , 181 , 182 ]. Currently the majority of the “omic” studies at all levels (gene, epigenetic, transcript, protein, metabolites) are correlative.…”
Section: Genomic Alterations/tumor Mutation Burden In Bcmentioning
confidence: 99%
“…5,6 To date, methylation signatures have been applied as cancer biomarkers due to their dynamic behavior across tumor stage and grade, stability between individuals and consistency within tissue specificity. 7,8 Some have already been identified in bladder tumor tissue and liquid biopsy samples. [9][10][11][12] Recently, an investigation conducted by our group revealed that the DNA methylation pattern of seven new genes was linked to an abnormal gene expression in breast tumor tissue samples and related to clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic dysregulation, namely, DNA methylation, refers to the mechanisms by which the cell phenotype can be reversibly affected without altering the DNA sequence 5,6 . To date, methylation signatures have been applied as cancer biomarkers due to their dynamic behavior across tumor stage and grade, stability between individuals and consistency within tissue specificity 7,8 . Some have already been identified in bladder tumor tissue and liquid biopsy samples 9–12 …”
Section: Introductionmentioning
confidence: 99%